A force of ones : - Herman, Stanley M. (Jossey Bass, 1994)
Management consultant Herman ( The People Specialists ) here argues that individual self-development can exponentially enhance corporate group programs and can improve your work satisfaction and career prospects. He cautions against self-deception, warns of the imperfect judgment of those in authority who "see you in . . . ways that depend as much on their own needs and biases as on your actual behavior" and provides exercises to develop psychological acumen. Herman urges individuals to initiate informal dicussions with their bosses in which they can develop mutual support by articulating each other's strengths and weaknesses. He calls attention to conflicts, stressing that contention is a normal dynamic in human relationships and not necessarily a sign of breakdown; he also concedes, however, that not all interface talks bring about reasonable resolutions: "If you don't hold the cards, you can lose, even if you play the hand well." Perhaps the most helpful section of the book considers power and politics. While disdaining "hardball players," Herman also realistically notes that if you "strongly disapprove of politics, you probably won't get to be a CEO."